Development of innovative infrastructure in terms of the "SMART CITY" concept - Mishkina, Ruslana (Бескиди, 2019)
Today, the key task is to create the conditions for the development of cities of all types, ensuring that economic and social development of the country's territories is balanced by increasing its competitiveness. Thus, the task of creating conditions for the development of modern cities as intellectual centers providing in practice the priority of information and non-material parameters of urban development (urban software) over traditional material elements (urban hardware) [3], transforming them into "smart cities" ("smart city ").
Keywords: smart city; the developments; smart economy; the concept of a smart city; 72.01:338.49